Computer method for describing technologies and properties of thermoelectric materials based on Bi2-Te3 obtained by pressing - Rybchakov, D.E.; Serbyn, M.V. (Journal of Thermoelectricity, 2021)
This paper presents the results of a study of literary sources describing the technologies and properties of thermoelectric materials obtained by pressing. The results of one of the stages of creating a software product for describing the technologies for obtaining and properties of thermoelectric materials based on Bi-Te compounds are presented. Bibliography 13 Fig. 2, Table 1.